"But I Have a Pacer … There Is No Point in Engaging in Hypothetical Scenarios": A Non-Imminently Dying Patient's Request for Pacemaker Deactivation - Tracy, Bridget A. (Cambridge quarterly of healthcare ethics, 2025)
In this case report, we describe a woman with advancing dementia who still retained decisional capacity and was able to clearly articulate her request for deactivation of her implanted cardiac pacemaker - a scenario that would result in her death. In this case, the patient had the autonomy to make her decision, but clinicians at an outside hospital refused to deactivate her pacemaker even though they were in unanimous agreement that the patient had capacity to make this decision, citing personal discomfort and a belief that her decision seemed out of proportion to her suffering. We evaluated her at our hospital, found her to have decision-making capacity, and deactivated her pacer resulting in her death about 9 days later. While some clinicians may be comfortable discussing patient preferences for device deactivation in patients who are imminently dying, we can find no reports in the literature of requests for device deactivation from patients with terminal diagnoses who are not imminently dying.